MAKANAN IKAN JAPUH, Dussumieria acuta Valenciennes, 1847 (FAMILI: CLUPEIDAE) DI PERAIRAN TELUK KENDARI [Food habit of rainbow sardine, Dussumieria acuta Valenciennes, 1847 (Family: Clupeidae) in Kendari Bay] - Asriyana Asriyana; M. F. Rahardjo; E. S. Kartamihardja; D. F. Lumban Batu (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2010)
Research on ontogenetic dietary variation rainbow sardine relating to body size of fish with time was carried out from August 2009 to January 2010 in Kendari Bay, Southeast Sulawesi. This research aims to describe ecological role of rainbow sardine in Kendari Bay. Fish collection was done using experimental gillnets (with different mesh sizes %, 1, 1%, and 1% inch) and scopednet (0 1 meter and mesh size 0.04 inch). A total of 136 individual fish were caught with range from 0.6 to 15.7 cm in length. Food analysis was determined by using Index of Preponderance. Result of the analysis indicates rainbow sardine is planktivora, which important diet is Bacillariophyceae. The male and females of fish did not have ontogenetic dietary (main food) shift and was not ontogenetic dietary shift relating to body size of fish. The diet of the fish every months was dominated by Bacillariophyceae.